Decoration of polylactic acid on graphene oxide for efficient adsorption of methylene blue and tetracycline. (May 2023) - Nouri, Alireza; Ang, Wei Lun; Mahmoudi, Ebrahim; Chua, Siew Fen; Mohammad, Abdul Wahab; Benamor, Abdelbaki; Ba-Abbad, Muneer M.; Leo, Choe Peng
Abstract: Decorating nanomaterials on graphene oxide (GO) can enhance its adsorption capacity and removal efficiency of water pollutants. In this study, for the first time, nano-sized polylactic acid (PLA) has been successfully decorated on the surface of GO through a facile synthesis approach. The adsorptive efficiency of GO-PLA for removing methylene blue (MB) and tetracycline (TC) from an aqueous solution was examined. The characterization confirmed the successful decoration of PLA on GO nanosheets with the nano size of PLA. It was hypothesized that the PLA was decorated on the surface of GO through covalent bonding between oxygen-containing functional groups and lactide molecules. The optimum adsorption parameters determined were at the adsorbent dose of 0.5 g L −1, pH 4, contact time of 120 min, and temperature of 318 K. The pseudo-second-order kinetic model described the contaminants' adsorption behaviour, and the intraparticle diffusion model revealed that both surface adsorption and intraparticle diffusion controlled the adsorption process. Langmuir isotherm model best described the adsorption behaviour of the pollutants on GO-PLA and demonstrated the maximum monolayer uptake capacities of MB (332.5 mg g −1 ) and TC (223.7 mg g −1 ). The adsorption results indicated that the uptake capacities of GO-PLA in comparison to GO have increased by approximately 70% and 110% for MB and TC, respectively. These observations reflect the remarkable role of nano-sized PLA that enhanced the adsorption capacity due to its additional functional group and larger surface area. Graphical abstract: Improvement in methylene blue and tetracycline removal by the decorated nano size PLA on graphene oxide. Image 1 Highlights: Nano-sized polylactic acid decorated on the surface of graphene oxide nanosheets. PLA was uniformly attached to oxygen-containing functional groups of GO. Adsorption efficiency of GO-PLA for removing pollutants was tested. Improved pollutant adsorption capacity of GO-PLA compared to GO was observed.